Revisiting Cytisus x praecox Bean (Leguminosae), a poorly known natural hybrid - Galán de Mera, Antonio; Linares Perea, Eliana (Mediterranean Botany, 2025)
Cytisus x praecox Bean, a hybrid between C. multiflorus (L’Hér.) Sweet and C. oromediterraneus Rivas Mart., T.E. Díaz, Fern. Prieto, Loidi & Penas, is described and discussed respect to the references about its artificial origin. Next to the material indicated as neotype, an epitype and isoepitypes are designated.